Acute Local Spontaneous and Profuse Gingival Hemorrhage during Neoadjuvant Treatment with Paclitaxel and Trastuzumab - Nima D. Sarmast; Maria J. Gutierrez Quevedo; Howard H. Wang; Estatio R. Gutierrez Herrera (MDPI AG, 2016)
This case report describes a 33-year-old female currently undergoing breast cancer treatment following the AC-T-T (doxorubicin hydrochloride (Adriamycin) and cyclophosphamide followed by paclitaxel (Taxol) and trastuzumab (Herceptin)) treatment regimen. Her chief complaint at the time of the emergency visit at the dental office was that she had an episode of profuse spontaneous bleeding located at the palatal gingiva in the maxilla between the left central and lateral incisor. To our knowledge, this is a novel finding related to the medications she is utilizing and should be further investigated.